Nintendo Wii Fit for balance rehabilitation in patients with Parkinson's disease: A comparative study. Issue 1 (January 2017) - Negrini, Stefano; Bissolotti, Luciano; Ferraris, Alessandro; Noro, Fulvia; Bishop, Mark D.; Villafañe, Jorge Hugo
Abstract: Background: Impaired postural stability places individuals with Parkinson's disease (PD) at an increased risk for falls. Objective: We evaluated the effectiveness of 10 vs. 15 sessions of Nintendo Wii Fit for balance recovery for outpatients PD. Methods: Twenty-seven patients, 48.1% female (66 ± 8 years), with PD. Patients with PD were consecutively assigned to one of two groups receiving either 10 or 15 sessions (low dose or high dose group, respectively) with Nintendo Wii Fit in recovering balancing ability. All outcome measures were collected at baseline, immediately following the intervention period, and 1-month following the end of the intervention. Main outcome measure: Falls risk test (FRT), Stability index (PST), Berg balance scale (BBS) and Tinetti scale. Results: The patients undergoing the 10 sessions demonstrated significantly improvement on the balance performances (Tinetti balance and gait scales, BBS and BSF) (all, P < 0.05) as those undergoing 15 treatment with Nintendo Wii Fit, but no significant group effect or group-by-time interaction was detected for any of them, which suggests that both groups improved in the same way. Conclusions: The results suggest that functional improvement can be made in fewer visits during outpatient rehabilitation sessions with Nintendo Wii Fit improving the efficiency of intervention.